Evaluación de la remoción de mercurio en aguas residuales, mediante la adsorción con cápsulas de borra de café gelificadas en alginato de sodio (2019)
The main purpose of this study was to evaluate the removal of contaminants in wastewater by adsorption, with coffee bean gel capsules in sodium alginate, using the crosslinking or crosslinking method, by which two molecules bond chemically generating polymers. To achive this, it was necessary to evaluate the effect of the encapsulation of coffee on adsorption, by making a comparison between the coffee bean powder and the coffee bean capsule, using separate tests with dyes and mercury, finding that there is no significant difference between the matrices of adsorption in terms of time and percentage of contaminant removal.